EFEKTIVITAS KANTONG BILANGAN TERHADAP KEMAMPUAN SISWA KELAS II MI BUSTANUL ULUM TEMPURAN DALAM MENGENAL MATERI NILAI TEMPAT - Febrianto Hidayat, Aji Pangestu; Fadilah, Yulina; Khosiah, Nur (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to evaluate the effectiveness of using number bags in improving students' understanding of place value material in class II MI Bustanul Ulum Tempuran. By using quantitative methods and involving 14 students as the population, data were collected through tests and documentation. Data analysis was conducted using pretest, posttest, normality test, and N gain test using SPSS 21.0 software. The research results show a significant improvement in material understanding, with an average pretest score of 41.4286 and a posttest score of 78.5714. However, the significance of the pretest at 0.208 and the posttest at 0.352 indicates that there is still room for further improvement in the effectiveness of using number bags in this context.